2014
DOI: 10.1182/blood-2013-08-522623
|View full text |Cite
|
Sign up to set email alerts
|

Comparative incidence of pregnancy outcomes in treated obstetric antiphospholipid syndrome: the NOH-APS observational study

Abstract: Key Points• Among women with pure obstetric APS, late pregnancy complications are more frequent in cases of prior fetal loss.• Late pregnancy complications are more frequent among women treated for pure obstetric APS than among nontreated controls.The incidence of pregnancy outcomes for women with the purely obstetric form of antiphospholipid syndrome (APS) treated with prophylactic low-molecular-weight heparin (LMWH) plus low-dose aspirin (LDA) has not been documented. We observed women without a history of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
116
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 30 publications
7
116
1
5
Order By: Relevance
“…In particular, antithrombotic therapy has been shown to be ineffective in preventing PE in women with APS. A recent study has shown that women with APS that received conventional LDA plus low-molecular weight heparin (LDA+LMWH) treatment throughout pregnancy had higher rates of PE than control women, suggesting that antithrombotic therapy is unsuccessful in preventing placental insufficiency and associated maternal and fetal risks (7). In this line, our mouse studies suggest that modulating inflammation might be a more effective approach than antithrombotic therapy (8).…”
Section: Introductionsupporting
confidence: 73%
“…In particular, antithrombotic therapy has been shown to be ineffective in preventing PE in women with APS. A recent study has shown that women with APS that received conventional LDA plus low-molecular weight heparin (LDA+LMWH) treatment throughout pregnancy had higher rates of PE than control women, suggesting that antithrombotic therapy is unsuccessful in preventing placental insufficiency and associated maternal and fetal risks (7). In this line, our mouse studies suggest that modulating inflammation might be a more effective approach than antithrombotic therapy (8).…”
Section: Introductionsupporting
confidence: 73%
“…2 With good treatment, approximately 70% of pregnant women with APS will deliver a viable live infant. 7 Very recently, Bouvier et al 8 confirmed this observation, reporting a live birth rate of 69.6% in a cohort of women with a purely obstetric APS who were treated with low-dose aspirin and low-molecular-weight heparin. In our unit, overall rates of live birth in women with aPL previously have been reported to be as high as 79%.…”
supporting
confidence: 54%
“…Consistently, patients at highest risk -those with triple aPL positivity and a history of thrombosis -have been reported to benefit from additional therapies in terms of pregnancy outcome: a 100% live birthrate was achieved when patients were treated with LDASA, full-dose LMWH, intravenous immunoglobulin, and low-dose steroids 19 . Most recently, the NOH-APS observational study showed that the obstetric outcome in women with APS receiving treatment depends upon the presenting manifestation: Women with prior late events are at higher risk for an adverse late outcome in the subsequent pregnancy than those with REM 20 . It can thus be envisaged that the clinical presentation might affect the therapeutic efficacy of treatment evaluated in obstetric APS: the standard regimen including LMWH and LDASA might be effective in low-titer aPL positive REM, but not effective enough in late events associated with high-titer aPL.…”
Section: Rheumatologymentioning
confidence: 99%